VALIDATION OF THE METHODS OF Hg DETERMINATION ON WASTE WATER TREATMENT PLANT SAMPLES USING COLD VAPOUR-ATOMIC ABSORPTION SPECTROPHOTOMETER (CV-AAS)TECHNIQUES - anggraini, Rika; Hairani, Rita; Panggabean, Aman Sentosa (JURNAL KIMIA MULAWARMAN; Vol 16 No 1 (2018)DO - 10.30872/jkm.v16i1.667, 2018)
The research about validation of the method of Hg determination on the sample from wastewater treatment plant (WWTP) PT. Badak NGL Bontang, Kalimantan Timur using cold vapour-atomic absorption spectrophotometer (CV-AAS) techniques has been conducted. To obtain a valid measurement result, determinations of the important several parameters that influence the method validation are used. The results of research showed that 20% SnCl 2 solution could be used as a reducing agent. The analytic performance of measurement obtain is good, showed with the linearity (r) value ≥ 0.995, LOD was 0.2530 ppb, LOQ was 0.8432 ppb, MDL was 0.6427 ppb and repeatability and reproducibility are shown as % RSD < 2/3 CV Horwitz values. The accuracy of this method is very good with a percentage of recovery value of 114.88%. Based on the results of this research, CV-AAS method can be used in the determination of Hg in WWTP samples with the valid results.